Simplified seismic analysis of flexibly supported two-way asymmetric-plan buildings. Issue 1 (17th January 2021) - Halabian, Amir M.; Teymoorian, Ehsan
Abstract : The seismic response of flexibly supported asymmetric-plan structures to severe ground excitations is affected by the interaction of translational and torsional responses of the superstructure and the deformation of the soil underlying the foundation. An innovative simplified method based on uncoupled modal response history analysis (UMRHA) is proposed for soil–two-way asymmetric-plan building systems excited by bi-directional ground motions. A new five degrees of freedom (5DoF) modal stick is introduced to represent the modal equations of the flexibly supported structure. All of the elastic properties in the 5DoF modal sticks are determined by converting the equation of motion of the whole soil–structure system into 8DoF modal equations. The results obtained from the proposed enhanced UMRHA method with the 5DoF modal stick were compared with those obtained from the UMRHA method by solving eight coupled modal equations of motion, conventional modal analysis and rigorous exact analysis. The results demonstrated the high efficiency of the proposed procedure in the evaluation of engineering design parameters.